Participation of the Army of the Republic of Peru in Public Security Tasks in Support of the National Police, From the Experiences of Mexico and Colombia - HURTADO NORIEGA, CARLOS (2019)
The participation of the Armed Forces in public security tasks is a recurring theme worldwide today, more nations are using it in support of the Police or as a direct task, because this looks absolutely surpassed or due to the increase in indications of institutional corruption. In the unique case of the Republic of Peru, the Armed Forces, specifically the army, has been participating in some tasks to support the National Police, in order to combat internal threats. Many of these tasks are covered by legal devices; however, there is a popular clamor, in addition to requests from some sectors of the State to participate in combating organized crime and common crime, which has no legal framework. In this sense, the investigation focuses on analyzing the possibility of the army fighting organized crime, because the last three governments have failed in their attempt and their strategies have not generated the expected results; on the contrary, this scourge has increased. Regarding the methodology, the qualitative method was used, specifically the classic hermeneutical design, because the information collected for the analysis focused on the new roles, budgets, strategies and legal framework, also considering the cases of countries such as Mexico and Colombia, in order to determine whether the participation of the army in public security tasks is a convenient alternative.